2019
DOI: 10.1186/s13014-019-1386-x
|View full text |Cite
|
Sign up to set email alerts
|

Effect of modern high-dose versus standard-dose radiation in definitive concurrent chemo-radiotherapy on outcome of esophageal squamous cell cancer: a meta-analysis

Abstract: Background and objectives Radiation Therapy Oncology Group (RTOG) 94–05 has demonstrated that higher dose radiation didn’t improve outcome of patients with esophageal cancer (EC). However, several retrospective studies showed that a higher dose radiation based on modern radiotherapy techniques could improve overall survival (OS) and local control rate (LCR) of patients with EC, especially esophageal squamous cell cancer (ESCC). As trials have provided updated and controversial data, we performe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
18
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 36 publications
(22 citation statements)
references
References 29 publications
1
18
0
Order By: Relevance
“…For patients with esophageal cancer receiving CCRT, the recommended radiation dose remains controversial. Although several meta-analyses were published regarding the optimal radiotherapy dose of CCRT for esophageal carcinoma (26)(27)(28), the robustness of their findings was inadequate due to the limited sample size. Moreover, some outdated radiation techniques, including the improper multiple field technique, cobalt-60 equipment, and 2D-CRT, were included in these studies, introducing more heterogeneity.…”
Section: Discussionmentioning
confidence: 99%
“…For patients with esophageal cancer receiving CCRT, the recommended radiation dose remains controversial. Although several meta-analyses were published regarding the optimal radiotherapy dose of CCRT for esophageal carcinoma (26)(27)(28), the robustness of their findings was inadequate due to the limited sample size. Moreover, some outdated radiation techniques, including the improper multiple field technique, cobalt-60 equipment, and 2D-CRT, were included in these studies, introducing more heterogeneity.…”
Section: Discussionmentioning
confidence: 99%
“…In contrast, one randomized and four non-randomized studies concluded that radiochemotherapy plus cetuximab was associated with considerable toxicity [ 28 , 30 , 31 , 35 , 36 ]. The non-randomized studies used radiochemotherapy regimens different from the two most common regimens [ 2 , 3 ].…”
Section: Discussionmentioning
confidence: 99%
“…Another study by Chen et al analyzed 18 articles and also found that a dose of ≥ 60 Gy appeared to improve OS and LRC, notably in Asian patients [32] . Luo et al reached a similar conclusion [33] . In spite of this, the studies analyzed in these three meta-analyses included many series implementing 2D radiation techniques, which may not reflect the real impact of dose-escalation in modern practice and planning.…”
Section: Discussionmentioning
confidence: 61%